Quantitative versus qualitative : complement or contradiction / Nagarajah Lee - Lee, Nagarajah (Universiti Teknologi MARA Sarawak, 2003)
This article discusses methodological pluralism as an alternative approach to conducting research in the social sciences. This discussion arises from fervent debate on quantitative versus qualitative methods that has taken place since the 1960s. The various theories relating to the quantitative and qualitative methodology are highlighted in order to show the reader the root cause of this debate. The strengths as well as the weaknesses of the quantitative and qualitative paradigms are also discussed, to throw light on why the mixed- methodology approach is a crucial issue to discuss. While stressing the unifying process, this article also presents a framework for a mixed methodology method. Finally this article also addresses the various reasons for calling for a mixed methodology approach as well as some criticisms of this move.